1996
DOI: 10.1029/95wr02974
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Wetting Front Movement During One‐Dimensional Infiltration into Soils

Abstract: The Green‐Ampt and Philip infiltration models are simplified with a capillary tube representation of porous media that can predict wetting front movement during horizontal and vertical infiltration into dry or initially moist soil. The simple model captures the fundamental physics of unsaturated fluid flow and reduces the number of parameters that must be measured. The relevant parameters are the air‐liquid interfacial tension, the density and viscosity of the liquid, the initial saturation, and the permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
2
37
0
1
Order By: Relevance
“…The NAPL retention behavior can then be connected with entirely fundamental physical parameters. Kao and Hunt (1996) further reinforce this concept that a capillary pore-scale viewpoint can be employed to explain NAPL movement, requiring only a minimum of phenomenological parameters. McBride et al (1992) also showed how the relative absorption behavior of NAPL can be compared using a simple capillary model.…”
Section: Spill Disappearancesupporting
confidence: 56%
See 1 more Smart Citation
“…The NAPL retention behavior can then be connected with entirely fundamental physical parameters. Kao and Hunt (1996) further reinforce this concept that a capillary pore-scale viewpoint can be employed to explain NAPL movement, requiring only a minimum of phenomenological parameters. McBride et al (1992) also showed how the relative absorption behavior of NAPL can be compared using a simple capillary model.…”
Section: Spill Disappearancesupporting
confidence: 56%
“…A more extensive and updated explanation of this subject is given by Dullien (1992). Kao and Hunt (1996) provide a useful table of values related to particle sizes. The information is sufficient to cover a great variety of granular porous media.…”
Section: Intrinsic Permeabilitymentioning
confidence: 99%
“…The higher sorptivity of the fracture surface zone of each rock was qualitatively revealed in the imbibition experiments conducted such that water enters directly into both the surface zone and bulk matrix (as in Figure 2a Results of the imbibition experiments on the highly waterwettable ceramics showed no significant differences in the B parameter relative to the mean value of 0.5 (Figure 7), indicating that scale effects were not responsible for discrepancies between measured and calculated permeabilities. The fact that values of B = 0.5 were obtained for these fused matrix ceramics also suggests that this parameter is not strongly specific to pore geometry, since the data used by Kao and Hunt [1996] were all from granular porous media. Thus wettability appears to be the most general potential limitation of using (5b).…”
Section: Resultsmentioning
confidence: 94%
“…Le facteur de forme p est tel que 0 < p < 1 (HAVERKAMP et ai, 1994) mais p devrait être constant pour des milieux poreux à structures similaires (CINDY et JAMES, 1996). D'ailleurs HAVERKAMP et al (1994), SMETTEM et al (1995) ont pris, pour des sols limono-sableux et sablo-limoneux (Redlands) respectivement P = 0,56 et p = 0,60.…”
Section: -Approche Théoriqueunclassified